Особенности построения модели речевого общения пользователя с многофункциональным сервисным мобильным роботом - Васильева, Н.Б.; Сухоручкина, О.Н.; Яценко, В.В. (Управляющие системы и машины, 2015)
Описано формирование базы данных и знаний для генеративной модели интерпретации речевого сигнала в рамках предметных областей. Предложен подход для упрощения пошагового диалога человека и многофункционального мобильного робота. Рассмотрена структура, позволяющая оперировать предметными областями, языками, типами смыслов и предложений в результате генерирующие соответствующие естественно языковые тексты. Описано формування бази даних та знань для генеративної моделі інтерпретації усномовного сигналу в межах предметних областей. Запропоновано підхід до спрощення покрокового діалогу між людиною та багатофункціональним мобільним роботом. Розглянуто структуру, яка дозволяє оперувати предметними областями, мовами, типами сенсів та речень, які в результаті генерують відповідні природномовні тексти. Introduction. Service mobile robots for everyday operation are in great interest of developers and market, which brings interaction between user and a machine to the foreground. The most natural way of human communication is a spoken dialogue. Meanwhile, current robotic systems may provide only formalized command spoken elements. Therefore, we propose away to introduce natural speech man–machine interaction based on the experience of a speech technology development. The purpose of research is to provide a spoken communication between a person and a mobile robot by means of generative model for the speech signal understanding within subject areas. Results. We consider exchange of the utterances as a step-by-step sentence/meaning type initialization. These constructions are specified by an expert, who forms the data and knowledge base for a subject area. We introduced a way to specify a common structure imperatives, questions and state reports. The result of a speech understanding is delivered to a robot, and the robot, in turn, passes back to the system a request for further task detalization or reports on its state. Acoustic model efficiency is crucial for both speech-to-text conversion and speech understanding even more. Therefore, we explore the influence of the several speech patterns on recognition accuracy. Conclusions. It is shown that the generative model for speech understanding can be applied to human-machine natural communication system development. Speech recognition/understanding accuracy may be improved on account of the speech pattern base model selection.